Experimental tests on slip factor in friction joints: comparison between European and American Standards - Emanuele Maiorana; Paolo Zampieri; Carlo Pellegrino (Fracture and Structural Integrity)
Friction joints are used in steel structures submitted to cyclic loading such as, for example, in steel and composite bridges, in overhead cranes, and in equipment subjected to fatigue. Slip-critical steel joints with preloaded bolts are characterized by high rigidity and good performance against fatigue and vibrational phenomena. The most important parameter for the calculation of the bolt number in a friction connection is the slip factor, depending on the treatment of the plane surfaces inside the joint package. The paper focuses on the slip factor values reported in European and North American Specifications, and in literature references. The differences in experimental methods of slip test and evaluation of them for the mentioned standards are discussed. The results from laboratory tests regarding the assessment of the slip factor related to only sandblasted and sandblasted and coated surfaces are reported. Experimental data are compared with other results from the literature review to find the most influent parameters that control the slip factor in friction joint and differences between the slip tests procedures.